Hitherto untold - Anderson, Galusha (Cochrane Pub. Co., 1910)
The silver caster -- Sheep in other folds -- Inherited appetite -- Conversion through affliction -- Words worthless without example -- Flatter your face -- A river man converted -- Covetousness ridiculed -- Tenpins -- A visit to Richmond in 1859 -- A Lubber's look -- "And Sally came" -- The fading nose -- Circumstantial evidence -- Flowers in desert places -- Special providence -- Grace versus wine -- Shouting and salvation -- Enlightened by Sumter's fall -- Fanning a wounded rebel -- Suffering by a minute -- A child converted by Scripture -- Preaching before prayer -- Lilies among thorns -- On granite -- Four drunkards -- A fugitive slave -- Beecher at the Twin Mountain House -- The late hon. Leland Stanford -- Reminiscences of Spurgeon -- Lee foresees Grant's triumph -- A reminiscence of Sherman and Grant -- New testimonies concerning Lincoln.